2014
DOI: 10.1177/0300060513496737
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal bupivacaine or levobupivacaine: Which should be used for elderly patients?

Abstract: Objectives: To compare two intrathecal anaesthetics, bupivacaine and levobupivacaine, for their effects on motor and sensory blockade and haemodynamics in patients aged !65 years undergoing transurethral resection of the prostate (TUR-P) or transurethral resection of the urinary bladder (TUR-M). Methods: Patients scheduled to undergo TUR-P or TUR-M were randomized to receive either 3 ml (15 mg) 0.5% isobaric levobupivacaine (group L) or 3 ml (15 mg) of 0.5% hyperbaric bupivacaine (group B) for spinal anaesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
4
6
1
1
Order By: Relevance
“…In our series of TCSA procedures, we reinforced the findings that the 2 local anesthetics, levo-bupivacaine and bupivacaine, are clinically comparable in terms of efficacy, potency, and hemodynamic response, as several studies have indicated during lumbar spinal anesthesia [ 37 , 38 ], lacking definitive assumptions on the superiority of one over the other. Nevertheless, we identified a discrepancy in the cumulative dose of neuraxial local anesthetic used in the 2 groups, with a greater amount of drug consumed in the LA + M + K group.…”
Section: Discussionsupporting
confidence: 68%
“…In our series of TCSA procedures, we reinforced the findings that the 2 local anesthetics, levo-bupivacaine and bupivacaine, are clinically comparable in terms of efficacy, potency, and hemodynamic response, as several studies have indicated during lumbar spinal anesthesia [ 37 , 38 ], lacking definitive assumptions on the superiority of one over the other. Nevertheless, we identified a discrepancy in the cumulative dose of neuraxial local anesthetic used in the 2 groups, with a greater amount of drug consumed in the LA + M + K group.…”
Section: Discussionsupporting
confidence: 68%
“…However, in this research, the group of patients was very heterogeneous regarding the age, from 18 to 85 years [13]. Gulek et al established that there was no significant statistical difference between the type or dosage of the local anesthetic (bupivacaine and levopubivacaine) and arterial hypotension during spinal anesthesia in elderly patients [14]. By comparing the preoperative values of average arterial pressure and the values at the end of the SP, it was proved that the patients have higher preoperative MAP in relation to the last value of MAP during surgery.…”
Section: Discussionmentioning
confidence: 66%
“…The levobupivacaine and ropivacaine are an interesting alternative to racemic bupivacaine. In a study on comparison of intrathecal 3.0 mL isobaric levobupivacaine with 3.0 mL hyperbaric bupivacaine in elderly patients undergoing TURP or TUR of urinary bladder, Gulec D et al [17] showed that levobupivacaine has statistically significant (p = 0.0001) longer onset of maximum motor block time (9.84 ± 3.10 minutes) as compared to bupivacaine (6.49 ± 2.2 minutes). Erdil F et al [11] in their study on the effects of intrathecal levobupivacaine and bupivacaine in 80 elderly patients, came to the conclusion that although the degree of motor block was similar in both the groups, the time to maximum motor block was 19.1 ± 5.4 minutes in levobupivacaine group while it was 9.5 ± 4.2 minutes in bupivacaine group proving statistically significant longer onset of maximum motor block with levobupivacaine.…”
Section: Resultsmentioning
confidence: 99%